Depth Profiling of Ion-Implanted 4H–SiC Using Confocal Raman Spectroscopy - Ying Song; Zongwei Xu; Tao Liu; Mathias Rommel; Hong Wang; Yufang Wang; Fengzhou Fang (Crystals, 2020)
For silicon carbide (SiC) processed by ion-implantation, dedicated test structure fabrication or destructive sample processing on test wafers are usually required to obtain depth profiles of electrical characteristics such as carrier concentration. In this study, a rapid and non-destructive approach for depth profiling is presented that uses confocal Raman microscopy. As an example, a 4H−SiC substrate with an epitaxial layer of several micrometers thick and top layer in nanoscale that was modified by ion-implantation was characterized. From the Raman depth profiling, longitudinal optical (LO) mode from the epitaxial layer and longitudinal optical phonon-plasmon coupled (LOPC) mode from the substrate layer can be sensitively distinguished at the interface. The position profile of the LOPC peak intensity in the depth direction was found to be effective in estimating the thickness of the epitaxial layer. For three kinds of epitaxial layer with thicknesses of 5.3 μm, 6 μm, and 7.5 μm, the average deviations of the Raman depth analysis were −1.7 μm, −1.2 μm, and −1.4 μm, respectively. Moreover, when moving the focal plane from the heavily doped sample (~1018 cm−3) to the epitaxial layer (~1016 cm−3), the LOPC peak showed a blue shift. The twice travel of the photon (excitation and collection) through the ion-implanted layer with doping concentrations higher than 1 × 1018 cm−3 led to a difference in the LOPC peak position for samples with the same epitaxial layer and substrate layer. Furthermore, the influences of the setup in terms of pinhole size and numerical aperture of objective lens on the depth profiling results were studied. Different from other research on Raman depth profiling, the 50× long working distance objective lens (50L× lens) was found more suitable than the 100× lens for the depth analysis 4H−SiC with a multi-layer structure.